The Impact of Technology on Scenario Planning for Crisis Management in Small Schools - Sravan NEMANI (Journal of Advanced Research in Education, 2025)
This paper investigates the influence of technology in contingency planning and the success of scenario planning in preserving educational continuity in small institutions during unanticipated disturbances. Examining research from 1994 to 2024 across several academic databases using a comprehensive literature analysis, the report finds Results show that scenario planning improves institutional resilience. However, its application is still uneven because of policy-related, infrastructure, financial, and policy-related problems. The paper emphasizes how technology could enhance the results of scenario planning. It can be concluded that increasing crisis preparedness and guaranteeing sustainable educational continuity in small schools depend on adaptive leadership, digital transformation, and multi-stakeholder collaboration.